AUGMENTED REALITY PENGENALAN GEOGRAFI ATMOSFER BERBASIS ANDROID - ., Nadia; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2021)
The development of this augmented reality application is based on the visualization of the geographical Atmosphere learning subject and the conditions of the teaching materials applied to students there are still weaknesses in understanding the teaching materials because the knownledge obtained is still in printed books so that it creates a sense of boredom in students. The purpose of this research is to develop the level of interest and insight of students in the Atmosphere, especially on improving the memory of students through a game in the form of a quiz. The data method applied is thtough observation and interview techniques. The preparation of this application design uses the Markerless-Based Tracking method which is a method that does not require markers to display virtual objects. However, in this study the researchers limited it to the trial stage only. As for the use of Unified Modeling Language to describe how the augmented reality application works. In this study, researchers used a tool called Unity for application design and Adobe Illustrator as a design button. The results of the trials on this application can be installed on Android device and appearance unique.